A Comparative Study of Hypofractionated Radiotherapy Versus Conventional Radiotherapy for Early Glottic Cancer (T1-2N0M0) - Purohit, Bhuvnesh Narayan; Harsh, Satya Shankar; Tawri, Priya; Kumar, H.S.; Sharma, Neeti; Jakhar, Shankar Lal (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Cancer is a major health concern in India, with approximately 1.1 million cases diagnosed annually. Laryngeal cancer constitutes about 1% of the total cancer burden and accounts for 0.3% of all cancer deaths. Glottic tumors typically metastasize after directly invading adjacent structures with better drainage. Glottic cancer boasts a high cure rate, regardless of the treatment modality employed. Radiotherapy is generally favored in most centers despite comparable cure rates for selected T1 and T2 glottis tumors. This study aimed to compare the radiation-induced acute and late treatment-related toxicities of hypofractionated radiotherapy and conventional radiotherapy in early glottic cancer (T1-2N0M0). Material and Methods: This study was conducted at the Acharya Tulsi Regional Cancer Treatment and Research Institute, Sardar Patel Medical College, Bikaner. It included 50 histologically confirmed cases of early glottic cancer in patients under 70 years of age. Patients were treated with radiotherapy and randomized into two arms: Arm A (Study) and Arm B (Control). Arm A received hypofractionated radiotherapy (55 Gy/20 fractions in 2.75 Gy/fraction over 4 weeks) and Arm B received conventional radiotherapy (66 Gy/33 fractions in 2 Gy/fraction over 6.5 weeks). Voice quality and toxicities were assessed at the end of treatment and at 1, 2, 3, and 6 months follow-up. Data were analyzed using percentages, means, chi-square tests, and p-values. Results: The majority of patients were in their sixth decade of life and all were male. Most patients had an ECOG Performance Score of 1. Hoarseness alone was present in 46 (92%) patients, while 4 (8%) presented with hoarseness and dysphagia, which were comparable between groups. Histologically, all patients had squamous cell carcinoma (SCC). In the study arm, 11 (44%) patients were T1A, 9 (36%) were T1B, 4 (20%) were T2A, and 1 (4%) was T2B, compared to 5 (20%), 5 (20%), 10 (40%), and 5 (20%) respectively in the control arm. In the study arm, 25 (100%) patients received 58.4 Gy (2 GyEq), while in the control group, 15 (60%) received 66 Gy and the remaining 10 (40%) received 64 Gy. All 25 (100%) patients in both arms completed treatment. At the end of treatment, only 3 (12%) patients in the study arm and 5 (20%) in the control arm had normal voice. At the 1-month follow-up, 7 (28%) versus 9 (36%) patients; at the 3-month follow-up, 13 (52%) versus 15 (60%) patients; and at the 6-month follow-up, 21 (84%) versus 22 (88%) patients in the study and control arms respectively had normal voice (X2 = 1.026, p-value = 0.599). Grades of skin reactions, mucositis, and dysphagia decreased from 2 to 1 at the end of treatment, and further to 1 to 0 at 1, 3, and 6 months follow-up in both groups. Conclusion: Hypofractionated radiotherapy is a safe treatment modality with high local control rates, acceptable long-term toxicities, favorable voice outcomes, and symptomatic relief, offering the added advantage of a shorter treatment duration, which improves patient compliance.